Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4103/jpbs.jpbs_44_20
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of stress distribution in subcrestal placed platform-switched short dental implants in D4 bone: In vitro finite-element model study

Abstract: A BSTRACT The present study was carried out to assess stress distribution in the maxillary posterior bone region (D4 bone) with the help of a short platform switched subcrestal dental implants using the FEM model. Missing teeth surfaces related to the maxillary posterior region were stimulated. The bone model had a cancellous core of (0.5 mm) which represents D4 bone. A 7.5x4.6 mm screw type implant system with 3.5 platform switch abutment was selected. ANSYS WORKBENCH was used to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…It should also be noted that the stress observed in the cases of angled loading was always much higher than those observed in the cases of axial loading, reaching a ninefold increase in the case of the Ø3.75 implant and Type 0-I bone quality. These results are in accordance with those reported by Sesha et al, who also observed higher bone stress when the load was applied with a 30° angulation compared to vertical loading [ 29 ]. Same findings were obtained by Papavasiliou et al, who concluded that stresses under oblique loading were approximately 10 times greater than under axial loading [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…It should also be noted that the stress observed in the cases of angled loading was always much higher than those observed in the cases of axial loading, reaching a ninefold increase in the case of the Ø3.75 implant and Type 0-I bone quality. These results are in accordance with those reported by Sesha et al, who also observed higher bone stress when the load was applied with a 30° angulation compared to vertical loading [ 29 ]. Same findings were obtained by Papavasiliou et al, who concluded that stresses under oblique loading were approximately 10 times greater than under axial loading [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cortical bone, cancellous bone, and the implant with abutment were all assumed to be linearly elastic, homogeneous, and isotropic [ 11 ]. The corresponding elastic properties, such as Young’s modulus and Poisson’s ratio of cortical bone and implant, were determined according to a literature survey [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dimensions and properties for cortical bone, trabecular bone, and titanium implants were assigned to models (Figure 1 ). Each solid component with isotropic, homogeneous, and linearly elastic behavior was assigned its Young's modulus and Poisson's ratio (Table 1 ) [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Contrarily, the minimum principal stress was concentrated in the alveolar bone crest, yet with less intensity than in the SP-O group. The occurrence is due to the fact that the load was vertical and not oblique (Moura et al, 2020;Hong et al, 2020;Sesha et al, 2020). Due to the implant does not have a function in the study, this stress was dispersed through all the structure (Hajizadeh, Panahi, 2019;Brandão de Holanda et al, 2020).…”
Section: Discussionmentioning
confidence: 96%